MIDWIFERY CARE OF PREGNANCY: Mrs. H IN BLANG KRUENG VILLAGE, BAITUSSALAM DISTRICT, ACEH BESAR REGENCY IN 2025 - Rini Misfika; Berkat, Satrinawati; Yusnaini (Department of Midwifery, Health Polytechnic of Aceh, 2025)
The Maternal Mortality Rate (MMR) is a primary indicator for assessing the level of public health. The high MMR indicates the low quality of health services and the lack of awareness of mothers regarding the importance of pregnancy check-ups. One of the strategic efforts in reducing MMR is through the provision of high-quality and standardized midwifery care during pregnancy. The purpose of this case report is to carry out midwifery care for pregnancy on Mrs. H in Blang Krueng Village, Baitussalam District, Aceh Besar Regency, and document it in the form of SOAP. The first care was carried out on February 14, 2025. The results of the assessment showed that the general condition of the mother was good, 29 weeks of pregnancy, with complaints of swollen feet when standing for a long time and frequent urination at night. The physical examination and anamnesis yielded expected results. The care provided included education regarding the causes and treatment of complaints, third-trimester discomfort, signs of pregnancy danger, and high-risk pregnancy. The subject understood and accepted the explanation given and was willing to follow the recommendations. Subsequent visits will be conducted according to the pregnancy development schedule to monitor and provide appropriate follow-up care, supporting a healthy pregnancy.